Status of Climate Smart Aquaculture Practices in Ilorin West Local Government Area of Kwara State, Nigeria - Ifabiyi , J.O; Bello, O.G; Komolafe, S.E; Banjoko , I.K.; Ahmed , S.A2 (Iraqi Journal of Aquaculture, 2023)
This study examined the status of climate smart aquaculture practices (CSAP) in Ilorin West Local Government Area of Kwara State, Nigeria. About 120 fish farmers were selected for the study. Statistical tools such as frequency count, percentage, mean score, binary logistic regression and Pearson product moment correlation were used to analyse the data. The result revealed that the average age of the respondents was 45 years and 79.2% of them were males. About 65% of them had tertiary education with an average of 6 years’ experience in fish farming. The average annual income of the respondents was about 379. 25 Dollars, and the average household size was 5 persons. The result also showed that about 65% of the respondents used earthen ponds for fishing with an average of 8 fishing ponds per farmer. The most stocked species of fish was catfish (79.2%). Majority (88.3%) of the respondents owned the ponds used and about 90.8 % of them indicated that they farm on the pond all-year-round. About 87.5% of them had high status on the use of climate smart aquaculture practices. The result of binary logistic regression showed that pond type (b=1.350), source of stocked fish (b= 0.850), sources of credit (b= 0.456) and access to extension services (B=1.607) were the determinant factors of the use of CSAP. The study concludes that the main climate smart aquaculture practices used by the fish farmers were stocking of fish, liming of pond, feeding of fish, provision of measures, sorting of fish, water transparency farmers.